The Impact of Job Training, Education and Work Motivation on Employee Performance - Trijadi Herdajanto (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
An organizational unit's success depends on the variables that affect it, such as job training, education, and work motivation, according to efforts to increase employee performance. Management must play a part in carrying out successful and efficient work. The goal of this study is to examine the variables that can raise employee performance. Employee performance serves as the dependent variable in this study, with training, education, and motivation serving as the three independent variables. Using the census method, this study acquired 34 employees from the Brangkal Mojokerto printing company's objects. Primary data, which were gathered by giving out questionnaires to participants, were the type of data used in this study. Multiple linear regression is a data analysis technique. The test results demonstrate that education, training, and motivation all significantly impact employee performance.